Mixed Convection Flow along a Stretching Cylinder in a Thermally Stratified Medium - Swati Mukhopadhyay; Anuar Ishak (Journal of Applied Mathematics)
An analysis for the axisymmetric laminar boundary layer mixed convection flow of a viscous and incompressible fluid towards a stretching cylinder immersed in a thermally stratified medium is presented in this paper. Similarity transformation is employed to convert the governing partial differential equations into highly nonlinear ordinary differential equations. Numerical solutions of these equations are obtained by a shooting method. It is found that the heat transfer rate at the surface is lower for flow in a thermally stratified medium compared to that of an unstratified medium. Moreover, both the skin friction coefficient and the heat transfer rate at the surface are larger for a cylinder compared to that for a flat plate.